APPLICATION of TOTAL PRODUCTIVE MAINTENANCE to REDUCE NON-STICK ON PAD PROBLEM in a SEMICONDUCTOR INDUSTRY - Sivakumar, Dhar Malingam (2004)

(untitled)
Total Productive Maintenance (TPM) methodologies are used to eliminate profit loss or waste due to equipment failure or defect. In the participating semiconductor company one of the TPM pillars, which is Focus Improvement activity was employed to improve yield. The team focused on Non Stick on Pad (NSOP), which was the top yield lost contributor. Floating die contributed 48% of the NSOP defect. How Focus Improvement activity is used to reduce Non Stick on Pad due to floating die is shown. As a result NSOP due to floating die had been reduced from 1300 parts per million (ppm) to 650 ppm a reduction of 50% within one year.